O papel do Estado como executor de política industrial: uma análise comparativa entre Brasil e Índia - Silva, Gabriel de Oliveira e (2015)
This work aims to analyze two distinct processes of industrialization, Brazilian and Indian, with the parameter of the main development plans in both countries. Within the context of the so called import substitution industrialization, comparisons are made in the way public managers tried to break with the external dependence through different State experiences as developers of Industrial Policy, with special emphasis on the issue of funding and sustainability of industrial sectors of capital goods. An analysis of the results is presented, aiming to interpret and to relate in a critically way, the international integration of the two countries, noting that the good results are the consequence not of specific changes, but thanks to a diverse planning and various development plans